102 Oral iron supplementation in pregnancy in austria: haphazard usage. (20th August 2018) - Spary-Kainz, Ulrike; Semlitsch, Thomas; Rundel, Sophie; Avian, Alexander; Herzog, Sereina; Jakse, Heidelinde; Siebenhofer, Andrea
Abstract : Objectives: Iron-deficiency anemia is common in pregnancy, with a prevalence of about 16% in Austria. International guideline recommendations on regular anemia screening (none/once/twice) and treatment with iron preparations are inconsistent. Regardless of anemia screening guideline, recommendations for pregnant women might vary from routine intake with different daily dosages to no routine iron supplementation. The aim of our study was to identify how often pregnant women take iron or iron-containing multivitamin supplements, and to find out when they started and who recommended they do so. Method: This cross-sectional study was conducted at the Mother-Child-Booklet (MCB) service center of the Styrian Health Insurance Fund in Graz, Austria. A questionnaire with 7 questions was developed and piloted by our study team, a psychologist, and an expert from the MCB service center. The 7 questions covered existing anemia diagnoses, current intake of iron-containing supplements, details on who recommended taking them, dosages, brand names, and socioeconomic data. The sample size calculation was based on a pre-examination of 70 pregnant women that indicated that, assuming a dropout rate of 10%, 322 pregnant women would have to be included to reach the targeted sample size of 289. Absolute and relative numbers and corresponding 95% confidence intervals were calculated using bootstrapping techniques. The study was approved by the Medical University of Graz ethics committee. Results: 325 women completed the questionnaire. 62.1% were over 30 years of age, and for 51.7% it was their first pregnancy. 10.8% (n=35) were diagnosed with anemia before becoming pregnant. 72.9% (237/325, 95% CI: 67.7% to 77.8%) reported taking an iron or multivitamin supplement during pregnancy. 45 different products were taken, but 61% of women took one of three different supplements. Of the 185 women that were not diagnosed with anemia before becoming pregnant but reported taking an iron containing supplement, 78.4% (n=145) took it regularly and 28.1% (n=52) started before they knew they were pregnant. 88.6% (n=164) took supplements on the recommendation of their doctor. 11.9% (n=22) on the recommendation of family or friends and 4.9% (n=9) on the advice of a pharmacist. Conclusions: Overall, 67% of pregnant women in our cohort were taking iron-containing compounds, irrespective of whether they were deficient in iron or not. Doctors were predominantly responsible for advising them to take it. No standardized procedure is available on which to base the decision to take iron during pregnancy, even in guidelines. Much more information on the harms and benefits of iron supplements should be provided to health care professionals, pharmacists and pregnant women, so they can make an informed decision on whether to take them.